Rola rodziny a podejmowanie aktywności ruchowej przez studentów - Palacz, Justyna (Karkonoska Państwowa Szkoła Wyższa, 2012)
A rational organization of leisure time should be a priority for the family environment. This problem is particularly important in the era of modern civilization, dominated by passive forms of recreation, resulting in many hours spent sitting in front of the TV and the computer screen. The role of parents should be based on a conscious and deliberate preparation of children and young people for a proper organization of their leisure time. It is important that parents’ activities encourage young people to participate in individual and organized forms of physical activity (sport, tourism, and recreation). Previous studies clearly indicate thatphysical activity in childhood influences the physical activity in adulthood. The processesof awakening interest, searching for patterns of behavior and forming habits related to various types of physical activity are all elements of lifelong learning.
Keywords: aktywność fizyczna; rodzina; studenci